2013
DOI: 10.3389/fonc.2013.00080
|View full text |Cite
|
Sign up to set email alerts
|

Application of FDG-PET/CT in Radiation Oncology

Abstract: Positron emission tomography (PET)/computed tomography (CT), which combines the advantages of high sensitivity and specificity of PET and high resolution of CT, is a unique tool for cancer management. PET/CT has been widely used in cancer diagnosis and treatment. The article reviews the recent applications of PET/CT in radiation oncology, with a focus on 18F-fluorodeoxyglucose (FDG)-PET/CT, addressing the applications in treatment planning and treatment response assessment of radiation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 60 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…23 The advantages of combined anatomic and functional imaging have led to widespread adoption of PET/CT in RT clinics. 24 The growth in the number of PET/CT scanners in the Unites States increased approximately tenfold in a decade, 25 from approximately 200 in 2001 to more than 2500 in 2013. 26 Approximately 4% of the PET procedures were for RT treatment planning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 The advantages of combined anatomic and functional imaging have led to widespread adoption of PET/CT in RT clinics. 24 The growth in the number of PET/CT scanners in the Unites States increased approximately tenfold in a decade, 25 from approximately 200 in 2001 to more than 2500 in 2013. 26 Approximately 4% of the PET procedures were for RT treatment planning.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, [ 18 F]FDG‐PET/CT‐guided RT planning has seen increasing use in head and neck cancer, lung cancer, breast cancer, esophageal cancer, non‐Hodgkin’s lymphoma, gynecologic cancer, rectal cancer, and anal cancer . The advantages of combined anatomic and functional imaging have led to widespread adoption of PET/CT in RT clinics . The growth in the number of PET/CT scanners in the Unites States increased approximately tenfold in a decade, from approximately 200 in 2001 to more than 2500 in 2013 .…”
Section: Introductionmentioning
confidence: 99%
“…µPET-CT with 18 F-FDG is a functional imaging approach that provides unique molecular and metabolic information of tissues and organs based on glucose uptake capacity [30,37]. There remain some clinical concerns of biological risk of these combined PET/CT imaging, but it is still considered a powerful tool for clinical diagnostics [37]. Most tumors and inflammatory lesions lesion have increased uptake of 18 F-FDG owing to enhanced glucose utilization [29,37].…”
Section: Discussionmentioning
confidence: 99%
“…There remain some clinical concerns of biological risk of these combined PET/CT imaging, but it is still considered a powerful tool for clinical diagnostics [37]. Most tumors and inflammatory lesions lesion have increased uptake of 18 F-FDG owing to enhanced glucose utilization [29,37]. More recently, several studies have examined the ability of 18 F-FDG uPET-CT imaging to assess radiation damage [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical images lack the sensitivity to define tumor extent and the capacity to evaluate the biology of the tumor and normal tissue. Several studies have indicated that FDG-PET/CT increases the agreement between biopsies and delineated tumor volume and has the potential to impact the course of treatment [ 12 , 13 ]. In external beam radiotherapy and brachytherapy, accurately defining disease areas is critical to avoiding normal tissue.…”
Section: Discussionmentioning
confidence: 99%